PREVALENCE OF REFRACTIVE ERRORS IN ADOLESCENTS IN OUT- PATIENT ATTENDEES OF THE PREVENTIVE OPHTHALMOLOGY CLINIC OF COMMUNITY MEDICINE, S K I M S, KASHMIR, INDIA - Rohul, Jabeen; Maqbool, Aakifa; Hussain, Syed Arshad; Shamila, Hamid; Anjum, Fazli; Hamdani, Zahoor Ahamad (Journal of Health and Allied Sciences NU, 2013)
Blindness is one of the most significant social problems in India with uncorrected refractive errors as the second major cause accounting for 19.7% of blindness and low vision.All adolescents (12-18 years) attending the eye clinic from Jan 2007-Jan 2009 for any eye ailment were examined and screened for refractive error using Snellen's chart.Out of total 930 adolescents, 508(54.62%) of adolescents had refractive errors. Of the total males and females examined 57.43% and 52.12% respectively had refractive errors. The mean age of presentation was 14.3 years. Most of the adolescents presented with myopia 257(50.59%) followed by astigmatism (35.23%) and hypermetropia (14.17%).High prevalence of refractive errors warrants early detection and treatment.
Keywords: Refractive errors; adolescents; hypermetropia; myopia; astigmatism